Pemanfaatan Augmented Reality Sebagai Media Pembelajaran Pengenalan Buah-Buahan - Pramono, Anang; Setiawan, Martin Dwiky (Universitas Nusantara PGRI Kediri, 2019)
The concept of education for children is important. The aspects that must be considered are methods and learning media. In this research innovative and alternative learning media are made to understand fruits for children with Augmented Reality (AR). Augmented Reality (AR) in principle is a technology that is able to combine two-dimensional or three-dimensional virtual objects into a real environment and then project it. This learning media combines picture cards and virtual reality. Markers contained on picture cards will be captured by the mobile device camera, processed and will 3D animated pieces appear on the mobile screen in realtime. By using the concept of combining real world, real images on cards and virtual, applications can stimulate imagination and sense of desire in children and motivation to learn more and more. 3D fruit estimation created using the 3D Blender application and the Augmented Rea process lity is made using Unity and the Vuforia SDK library. The application of fruit recognition has been applied to several child respondents and has been tested on several types and brands of Android-based mobile phones. Based on research trials, 86% of 30 respondents stated that the application which was developed very effectively as a medium for the introduction of fruits.